Bentuk Koreografi Tari Golek Gonjing Miring Karya Dona Dhian Ginanjar S.Sn. - Grace Stella Amoreta Lomi; Eny Kusumastuti (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The Golek Gonjing Miring Dance is one of the classical dance works created by Dona Dhian Ginanjar in 2019. This work is interesting to study because it combines two classical Javanese dance styles, namely the soft and feminine Surakarta style and the firm and masculine Yogyakarta style, as a symbol of the duality of women's nature. The theme of this dance tells the story of the angels who came down from heaven to have fun on earth, which is visualized through smooth and expressive choreography with a variety of traditional movements. The accompanying music uses Gendhing Ladrang Gonjing Miring Laras Pelog Nem, which supports the mystical and graceful atmosphere in the performance. Supporting aspects such as make-up, costume design, stage design, and lighting design also strengthen the delivery of artistic and symbolic meaning in this work. This study aims to describe the choreographic form of the Golek Gonjing Miring Dance, musical structure, and supporting visual elements that form an aesthetic unity in the performance. The results of the study show that the Golek Gonjing Miring Dance is not only a medium for preserving Javanese classical dance culture, but also a form of innovation that represents female characters in a more complex way.